Mendidik Karakter Siswa Hindu Berlandaskan Tri Hita Karana: Penelitian - Wayan Budiagus Putrayasa, I; Wayan Windayani, Ni; Made Hariawan, I; Putu Ayu Intan Lestari, Ni; Wayan Suhendrawiati, Ni (Jurnal Pengabdian Masyarakat dan Riset Pendidikan, 2025)
This research aims to understand how the Tri Hita Karana teachings are applied in forming the character of Hindu students at the high school level. The values ​​of Tri Hita Karana include harmonious relationships between humans and God (parhyangan), humans and each other (pawongan), and humans and the environment (pabelasan). The research was conducted using a descriptive qualitative approach through observations and interviews at one of the high schools in Bali which has a Hindu religious education program. The research results show that applying the Tri Hita Karana values ​​can foster religious character, discipline, care for the environment and respect for others. The obstacles faced are the lack of consistency in implementation outside the school environment and the influence of modern lifestyles on student behavior. Therefore, collaboration between teachers, parents and the community is important in strengthening character education based on Hindu teachings.